An Analytical Study of Intelligence in the Makkī Era - Al Azhari, Abdul Wahab Jan (Journal of Islamic and Religious Studies, 2019)
Security is most important need of every state and community. Surveillance and keeping eye on the enemy are the core responsibilities of every state. All the absolute qualities of a leader can be found in The Holy Prophet (P.B.U.H). Therefore, the first nucleus of security education was in Makkah and expanded with the expansion of the Da’wah till the declaration of Madina as a Islamic state. There are various studies on the subject of surveillance, but they did not cover all aspects of Sīrah in Makkī era regarding the various steps and methods of surveillance. This article investigates how the Holy Prophet (P.B.U.H) maintained the security measures during Makkī era to ensure the security of all his companions and followers. In the First section of this article definition and history of intelligence was discussed, followed by the various techniques of surveillance used in different occasions by the Prophet (P.B.U.H). The last section of the article focused on the techniques used in Makkī era. The article further elaborates the practical steps taken by Prophet (P.B.U.H) to secure his companions and their families from the opponents to the extent possible, like migration to Habash and finally to Madina which concluded in establishment of a free state for Muslims.